Estado y poder: una visión de América Latina en el siglo XX - Alvarez, Servando A. (2006)
After Colonial period had been ended, Latin America faced its main problem: the construction of political system under Independence’s ideas. No elements from this recent past might be used to built a Nation-State in European way for organizing a civil society. Most of actual Latin America political problems in several countries at the beginning of 21st century, came up from the old century ones, and this fact support a reviewing of interdisciplinary foundations from “The modern and democratic Law State” are supported. This paper aim to discuss such a point of view.